Analisis Sistem Kompensasi Menggunakan Metode Overlapping Pada UKM Bakery X - Dewa Ayu Made Safira Dwiyani; Muhammad Alfaridzi Samallo; Farah Fauziyyah; Revina Novri Azahra; Aviliani Margaretha Sipahutar (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2025)
The bakery industry in Indonesia continues to grow as public consumption increases. However, many bakery SMEs face challenges in implementing a fair compensation system. One of them, SME Bakery X, has difficulty adjusting its payroll structure to the prevailing minimum wage standard. This study analyzed SME Bakery X's employee compensation system using the overlapping method to determine whether this method creates a fairer and flexible payroll structure. In addition, this study compared the resulting compensation system with the UMP and UMK to assess its suitability. This research used a qualitative method with a case study approach. Data were obtained through interviews with business owners and employees and secondary data analysis. The total sampling technique was applied to 20 employees. Analysis was conducted using salary mapping and overlapping methods to evaluate the pay gap and design a fairer compensation system. The results showed that all employees of SME Bakery X received salaries below the Bogor Regency MSE, and 45% below the West Java UMP. After implementing the overlapping method, there was an increase in compensation for some positions, with the highest growth of 24.03%. This method improved job satisfaction and helped SME Bakery X retain a quality workforce